The captive maiden - Dickerson, Melanie (Dickerson, Melanie. Hagenheim series., 2013)
In this story loosely based on the Cinderella fairy tale, Gisela is determined to get an invitation to the ball being thrown for the duke's son, Valten, but meeting him may not lead to her happily-ever-after.